A NEW HYBRID SYSTEM FOR RECOGNITION OF HANDWRITTEN-SCRIPT - Saeed, Khalid; Tabedzki, Marek (International Journal of Computing, 2014)
A new method for object recognition and classification is presented in this paper. It merges two well-known and tested methods: neural networks and method of minimal eigenvalues. Each of these methods answers for a different part of recognition process. Method of minimal eigenvalues makes preparatory stage of analysis – of coordinates of characteristic points we get the vector describing given image. Next, it is recognized and classified with neural network. Gathering of characteristic points we perform with our view-based algorithm, but other methods should also do. In this work, method was applied for words in Latin alphabet – handwritten and machine-printed. The obtained results are promising.